Resistance Training Safety during and after the SARS-Cov-2 Outbreak: Practical Recommendations. (24th September 2020) - Gentil, Paulo; de Lira, Claudio Andre Barbosa; Souza, Daniel; Jimenez, Alfonso; Mayo, Xian; de Fátima Pinho Lins Gryschek, Anna Luiza; Pereira, Erica Gomes; Alcaraz, Pedro; Bianco, Antonino; Paoli, Antonio; Papeschi, Julio; Carnevali Junior, Luiz Carlos
Abstract : In December of 2019, there was an outbreak of a severe acute respiratory syndrome caused by the coronavirus 2 (SARS-CoV-2 or COVID-19) in China. The virus rapidly spread into the whole world causing an unprecedented pandemic and forcing governments to impose a global quarantine, entering an extreme unknown situation. The organizational consequences of quarantine/isolation are absence of organized training and competition, lack of communication among athletes and coaches, inability to move freely, lack of adequate sunlight exposure, and inappropriate training conditions. The reduction of mobility imposed to contain the advance of the SARS-Cov-2 pandemic can negatively affect the physical condition and health of individuals leading to muscle atrophy, progressive loss of muscle strength, and reductions in neuromuscular and mechanical capacities. Resistance training (RT) might be an effective tool to counteract these adverse consequences. RT is considered an essential part of an exercise program due to its numerous health and athletic benefits. However, in the face of the SARS-Cov-2 outbreak, many people might be concerned with safety issues regarding its practice, especially in indoor exercise facilities, such as gyms and fitness centers. These concerns might be associated with RT impact in the immune system, respiratory changes, and contamination due to equipment sharing and agglomeration. In this current opinion article, we provide insights to address these issues to facilitate the return of RT practices under the new logistical and health challenges. We understand that RT can be adapted to allow its performance with measures adopted to control coronavirus outbreak such that the benefits would largely overcome the potential risks. The article provides some practical information to help on its implementation.